2012
DOI: 10.1007/s11832-012-0427-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relationship between joint laxity and migration of the hip in children with down syndrome

Abstract: This study showed no relationship between joint laxity and migration of the hip in children with Down's syndrome. This implicates that we were not able to prove that joint laxity is the major factor in developing hip migration in children with Down's syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
10
1
Order By: Relevance
“…Although generalized muscle hypotonia and ligamentous laxity may play a role, the hip is a deep and tridimensional complex joint whose stability is mostly influenced by the cartilaginous and bone anatomy. One study 8 reported no relationship between ligamentous laxity and the migration of the hip, suggesting that the joint laxity may not be the major risk factor for hip instability in Down syndrome. Hence, isolated soft-tissue procedures including capsular plication have a limited role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although generalized muscle hypotonia and ligamentous laxity may play a role, the hip is a deep and tridimensional complex joint whose stability is mostly influenced by the cartilaginous and bone anatomy. One study 8 reported no relationship between ligamentous laxity and the migration of the hip, suggesting that the joint laxity may not be the major risk factor for hip instability in Down syndrome. Hence, isolated soft-tissue procedures including capsular plication have a limited role.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ligamentous laxity and generalized muscle hypotonia, 6 - 8 there is a spectrum of skeletal anatomical abnormalities that might contribute to the hip instability in Down syndrome. 4 , 9 - 14 Abnormalities of the femur including increased femoral anteversion and coxa valga have been reported and have been described as the rationale for treatment by femoral intertrochanteric osteotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Since the study by Ehuis et al ., joint laxity has been known to be correlated with age 28 . This collinearity could induce multicollinearity in the model with instability and inaccuracy in the estimation of the RC.…”
Section: Methodsmentioning
confidence: 99%
“… 5 Whereas some studies have proposed joint laxity as a possible cause of hip instability, 5 , 6 others did not find a relationship between joint laxity and hip migration in DS patients. 3 , 7 Another plausible aetiological factor of hip instability might be muscular inbalance. 3 Children with DS portray delayed motor development, associated with muscle hypotonia, ligament laxity and cerebellar dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 7 Another plausible aetiological factor of hip instability might be muscular inbalance. 3 Children with DS portray delayed motor development, associated with muscle hypotonia, ligament laxity and cerebellar dysfunction. 8 Characteristics of motor dysfunction are longer reaction times, longer movement times and co-contraction of agonist-antagonist muscles.…”
Section: Introductionmentioning
confidence: 99%